1991
DOI: 10.3109/02699059109008108
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive rehabilitation: A neuropsychological speciality comes of age

Abstract: In its first decade cognitive rehabilitation has emerged from infancy with the energy and much of the turmoil of youth. It has become an established speciality in brain-injury rehabilitation and has inspired many neuropsychologists to broaden their expertise beyond diagnosis and address their efforts to intervention. Restoration, although controversial, is an important and valid goal at the outset of cognitive rehabilitation, whereas the substitution of other means of goal achievement and environmental redesig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Therefore, the ability to identify any functional impairment that may affect safety after a TBI is critical to prevention of re-injury. The utility of neuropsychometric testing in evaluating cognitive impairment resulting from TBI is well established [2][3][4][5][6]. However, comparatively little information is available on the performance of dynamic motor tasks following TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the ability to identify any functional impairment that may affect safety after a TBI is critical to prevention of re-injury. The utility of neuropsychometric testing in evaluating cognitive impairment resulting from TBI is well established [2][3][4][5][6]. However, comparatively little information is available on the performance of dynamic motor tasks following TBI.…”
Section: Introductionmentioning
confidence: 99%
“…The result is frequently a decrease, or loss, of income and earning potential, resulting in increased financial strain for the individual, and his or her family, over a lifetime (Khan et al 2003; Sarajuuri et al 2005). The consequences of TBI are social, emotional, and cognitive, affecting both the individual and his or her family (Gianutsos 1991). …”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there is no doubt that such techniques, whilst not influencing memory impairment, can certainly reduce the effects of such impairment and have positive benefits in terms of disability and handicap [22]. Similar approaches have been taken to the remediation of problem solving deficits, attention deficits and perceptual problems [23] Fortunately, very few individuals remain in prolonged coma or prolonged vegetative state following brain injury. One study [24] found that 0.6% of all brain-injured individuals admitted to a neurosurgical unit remained in prolonged coma (of more than two weeks' duration).…”
Section: Figure 6 Adaptive Devisesmentioning
confidence: 99%